Impact of an Educative-Supportive Nursing Programme on Self-Care Behaviour and Quality of Life of Female Students with Primary Dysmenorrhea - chailarp, kanokwan -; Lagampan, Sunee; Auemaneekul, Naruemom (Journal of Thailand Nursing and Midwifery Council, 2018)
Abstract: Objective: To fnd out how an educative-supportive nursing programme contributed to improving the self-care behaviour and quality of life of female students with primary dysmenorrhea. Design: Two-group experimental research with a pre-test and a post-test. Methodology: The sample consisted of 60 female students aged between 18 and 22, divided into a control group (30) and an experimental group (30). Only the experimental group participated in an 8-week educative-supportive nursing programme. Data were collected by means of a self-completed questionnaire, before the experiment, after the experiment (week 8) and during the follow-up (week 12). The data were analysed based on frequency, percentage, means, standard deviation, chi-square, independent t-test and repeated measures ANOVA. Results: After the experiment and during the follow-up period, the experimental group’s scores on self-care behaviour and quality of life were signifcantly higher than both their own pre-experiment scores and the control group’s (p-value < .05). The experimental group also displayed a signifcantly lower degree of menstrual pain than before the experiment, and than the control group did (p-value < .05). Recommendations: It is recommended that the use of this educative-supportive nursing programme, which was developed based on self-care theories, be promoted amongst women with primary dysmenorrhea as a means of relieving their menstrual pain and improving their quality of life during menstruation